Plasma proteomic changes in patients with non-valvular atrial fibrillation starting rivaroxaban treatment: A pilot study - Jean-Christophe Gris; Jean-Marc Monneuse; Laurent Borderie; Isabelle Metton; Géraldine Lavigne; Gilbert Skorski; Pierre Winum; Mathieu Granier; Guillaume Cayla (Thrombosis Update, 2021)
Introduction: Direct oral anticoagulants (DOACs) also influence cell signaling in various cell types, thus affecting biological systems other than coagulation, whose markers are uncertain. Material and methods: To perform a pilot study of variations in plasma protein by means of Liquid chromatography–high resolution tandem mass spectrometry (LC-HRMS/MS) in 5 patients with newly-diagnosed non-valvular atrial fibrillation (NVAF) starting rivaroxaban anti-FXa DOAC treatment. Results: A total of 260 proteins could be identified in plasma samples obtained before treatment and at one month of treatment. A significant sustained variation in their concentrations (doubling or halving) was evidenced in at least one patient. These variations were heterogeneous and inconstant from one patient to another. Their most striking feature was the downregulation of proteins participating in the inflammatory system reaction, and of proteins related to intravascular hemolysis. Other variations were rarer and more erratic. Conclusions: Individual rivaroxaban treatment-associated variations in protein were evidenced in patients with NVAF starting rivaroxaban. This should now be tested and confirmed with a large series of carefully annotated patients. Confirming these established variations would open the door to the search for clinically-relevant correlations and consequences, if any.